2007
DOI: 10.3989/gya.2007.v58.i2.77
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid DNA studies in <i>Lactobacillus plantarum</i> strains isolated from olive fermentations: production of and immunity to plantaricin OL15 is associated to a 9.6 Kb plasmid (pOL15)

Abstract: RESUMENEstudios de ADN plásmido en cepas de Lactobacillus plantarum aisladas de aceitunas fermentadas: La producción de y la inmunidad a plantaricina OL15 está asociada a un plásmido de 9.6 Kb (pOL15).En un estudio previo, se aislaron 12 cepas de Lactobacillus plantarum a partir de aceitunas fermentadas. Entre ellas, solo L. plantarum OL15 produjo bacteriocinas (plantaricin OL15). En este estudio, se examinó el contenido de AND plásmido en las 12 cepas citadas. Entre ellas, 9 cepas han mostrado de una a tres b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Similarly, Ruiz-Barba et al (1991) also showed that 35 L. plantarum strains isolated from different fermented green olive samples harboured large number of plasmids (from 5 to 16) ranging from 2 to 68 kb in size. A similarly wide variety of plasmid profiles in L. plantarum strains isolated from fermented olive samples was also reported by Mourad (2007).…”
Section: Resultsmentioning
confidence: 50%
“…Similarly, Ruiz-Barba et al (1991) also showed that 35 L. plantarum strains isolated from different fermented green olive samples harboured large number of plasmids (from 5 to 16) ranging from 2 to 68 kb in size. A similarly wide variety of plasmid profiles in L. plantarum strains isolated from fermented olive samples was also reported by Mourad (2007).…”
Section: Resultsmentioning
confidence: 50%
“…Plasmid DNA in the lactic acid bacteria is not always easily detected due to the copy number and isolation procedure (Mourad, 2007). In this study two kind of bacteriocin consist of plnB and plnEF were confirmed in the L. plantarum IBL-2 plasmid.…”
Section: Discussionmentioning
confidence: 70%